Water, Globalization, and Liberalization - Shoviani, Ari; Rodiyah, Rodiyah (Universitas Negeri Semarang, 2020)
Privatization, liberalization and globalization of water resources in Indonesia has become a complicated problem. In one hand, it will increase the economic values and investment but in the other hands it is contrary with the 1945 Constitution. Indonesian Water Resources Act has raised polemics and complaints from many parties, so that the proposed judicial review to the Constitutional Court. Finally, the Court cancelled this Act. This research is intended to analyse and describe the implementation of Water Resources Act that has been cancelled by the Court in the context of Friedman Theory, especially in Semarang City. The research emphasized and highlighted that the exploitation of water resources, as well as privatization and liberalization is not allowed by the 1945 Constitution.